VSC Adaptive Nonuniform Sampling Approach for Resource Optimization in Networked Controlled System - Andrej Sarjaš; Dušan Gleich (Proceedings of the International Conference on Applied Innovations in IT, 2025)
This paper presents an Adaptive Event-Triggered nonlinear Control method suitable for Networked Control Systems (NCS) with optimized resource exploitation. The work aims to ensure Networked Control Systems performance with lowered network usage and adaptive nonuniform controller execution. The nonlinear control strategy utilizes a predefined sliding variable, defined by system states and a nonlinear switching function, to maintain system stability within a specified boundary. This stability boundary is governed by an adaptive triggering condition, which balances system performance against network data-rate constraints and resource optimization. The adaptive triggering condition dynamically determines triggering law based on the state's metrics and auxiliary internal dynamics system. Internal dynamic systems guarantee the stability property of the NCS and leverage resource optimization for nonuniform control algorithm execution. The minimum inter-event time for a nonuniform approach is derived to address network limitations and controller computation burden. The effectiveness of the proposed NCS method is validated through experimental results on a real system with UDP communication protocol.